Promoting pupils' creative thinking in primary school mathematics: A case study. (March 2019) - Schoevers, Eveline M.; Leseman, Paul P.M.; Slot, Esther M.; Bakker, Arthur; Keijzer, Ronald; Kroesbergen, Evelyn H.
Highlights: More (different) creativity promoting strategies were used in 'open' maths lessons. Mathematical creativity was only promoted in 'open' maths lessons. Creation of an open atmosphere was related to creativity in open maths lesson only. Abstract: The importance of promoting mathematical creativity in education is increasingly acknowledged. Several strategies have been recommended to foster mathematical creativity such as creating an open atmosphere in the classroom, offering open lessons and possibly enriching mathematics education with ideas from other disciplines and experiences from out-of-school contexts. However, it is not yet clear in what way recommended pedagogical strategies promote pupils' mathematical creativity. Therefore, the purpose of this case study was to gain an in-depth understanding of promoting mathematical creativity in educational practice. To this end, interactions between a teacher and her 22 fourth-grade pupils in three different types of mathematics lessons were investigated. An 'open' in-school mathematics lesson, an 'open' out-of-school mathematicslesson and a regular ('closed') mathematics lesson were video recorded and interactions were transcribed verbatim. Subsequently, dialogic episodes were identified in the video transcripts and were coded on mathematical creative expressions of pupils and strategies used by the teacher. Furthermore, after each lesson the teacher was interviewed regarding her experiences with the given lesson. Interviews were audiotaped, transcribed verbatim and analysed by using constant comparison analyses. Findings indicate that mathematical creativity was only promoted in the two open mathematics lessons. More specifically, mathematical creative expressions were related to longer whole class dialogues in which the teacher created an open atmosphere; she created opportunities for pupils to express their ideas and took these ideas seriously. Although in some episodes of the regular mathematics lesson this open atmosphere was also created, no mathematical creativity occurred.